Investigation of recombination mechanisms in Cu(In, Ga)Se2 solar cells using numerical modelling. (1st November 2021) - Yang, Sheng; Khelifi, Samira; Wild, Jessica de; Vermang, Bart; Lauwaert, Johan
Abstract: In this work, recombination mechanisms are investigated in Cu(In, Ga)Se 2 solar cells based on numerical modelling and verified by regression analysis of the dark and light current density–voltage (J–V) curves. Loss mechanisms such as a back contact barrier, deep level defects in the absorber layer are determined by fitting the simulated cell performance with the measurements using global optimisation algorithm differential evolution. The cell performance in the fitting process includes J–V curves recorded at different temperatures and open-circuit voltage(V o c ) under different illumination intensities at 300K. The results show that for CIGSe solar cells with different preparation methods and absorber thickness, the main loss mechanisms are different. Based on the proposed numerical model and the observed loss mechanisms, suggestions are given for further improving the solar cell efficiency in each cell. Highlights: Surface, interface and bulk recombination mechanisms in CIGSe thin-film solar cells are distinguished by numerical modelling and regression analysis based on the solar cell performance. Global optimisation algorithm differential evolution is used in the regression analysis to avoid finding local minimal of the cost function. Good algorithmic performance and a convincing global minimisation are obtained in the fitting process. The recombination mechanisms are found to be different in CIGSe solar cells with different preparation methods and absorber thickness. The main loss mechanism in CIGSe solar cells with a relatively thick absorber layer is found to be the bulk recombination through deep level defects while in cells with an ultra-thin absorber layer is the back surface recombination. Based on the proposed numerical model and the observed loss mechanisms, suggestions are given for further improving the solar cell efficiency in each cell.